A touchdown bearing with surface waviness: Friction loss analysis. (April 2017) - Halminen, Oskari; Aceituno, Javier F.; Escalona, José L.; Sopanen, Jussi; Mikkola, Aki
Abstract: This paper presents a model for analysis of the chaotic turbulence in a touchdown bearing due to surface waviness. A multibody model of a bearing with surface waviness is presented. The model estimates the work done by the friction forces between the bearing components. Different waviness orders in the bearing inner and outer ring are examined by analyzing the friction losses in the touchdown bearing. The obtained results are compared with results reported in the literature. The proposed model supports selection of appropriate surface manufacturing accuracy for touchdown bearings to mitigate undesirable effects from surface waviness in a potential contact event. Graphical abstract: Highlights: A detailed multibody model of a touchdown bearing with surface waviness is presented. The model is used for detailed estimation of the work done by the friction forces. Different waviness is examined in the bearing inner and outer ring, and in the rotor. The obtained results are compared with results reported in the literature. The model supports selection of manufacturing accuracy to decrease heat generation.